Atrial fibrillation cryoablation is an effective day case treatment: the UK PolarX vs. Arctic Front Advance experience - Honarbakhsh, Shohreh; Martin, Claire A; Mesquita, Joao; Herlekar, Rahul; Till, Richard; Srinivasan, Neil T; Duncan, Edward; Leong, Fong; Dulai, Rajdip; Veasey, Rick; Panikker, Sandeep; Paisey, John; et al. (Oxford University Press, 2023)
Aims: Pulmonary vein isolation (PVI) is the cornerstone of catheter ablation for atrial fibrillation (AF). There are limited data on the PolarX Cryoballoon. The study aimed to establish the safety, efficacy, and feasibility of same day discharge for Cryoballoon PVI. Methods and results: Multi-centre study across 12 centres. Procedural metrics, safety profile, and procedural efficacy of the PolarX Cryoballoon with the Arctic Front Advance (AFA) Cryoballoon were compared in a cohort large enough to provide definitive comparative data. A total of 1688 patients underwent PVI with cryoablation (50% PolarX and 50% AFA). Successful PVI was achieved with 1677 (99.3%) patients with 97.2% (n = 1641) performed as day case procedures with a complication rate of <1%. Safety, procedural metrics, and efficacy of the PolarX Cryoballoon were comparable with the AFA cohort. The PolarX Cryoballoon demonstrated a nadir temperature of −54.6 ± 7.6°C, temperature at 30 s of −38.6 ± 7.2°C, time to −40°C of 34.1 ± 13.7 s, and time to isolation of 49.8 ± 33.2 s. Independent predictors for achieving PVI included time to reach −40°C [odds ratio (OR) 1.34; P < 0.001] and nadir temperature (OR 1.24; P < 0.001) with an optimal cut-off of ≤34 s [area under the curve (AUC) 0.73; P < 0.001] and nadir temperature of ≤−54.0°C (AUC 0.71; P < 0.001), respectively. Conclusions: This large-scale UK multi-centre study has shown that Cryoballoon PVI is a safe, effective day case procedure. PVI using the PolarX Cryoballoon was similarly safe and effective as the AFA Cryoballoon. The cryoablation metrics achieved with the PolarX Cryoballoon were different to that reported with the AFA Cryoballoon. Modified cryoablation targets are required when utilizing the PolarX Cryoballoon.